A SYSTEMATIC REVIEW OF POTENTIAL PHYTOCHEMICAL COMPOUND BARK OF PARAMERIA LAEVIGATA ON BIOFILM FORMATION - ANGGRAINI, WIRDA; PURWANTO, DJOKO AGUS; ISNAENI; KUSUMAWATI, IDHA; SURYANTO (International Journal of Applied Pharmaceutics, 2022)
Objective: Infectious disease is one of the problems in the health sector that continues to grow from time to time. Microorganisms can differentiate and develop in complex ways to form new morphologies that grow on the surface, known as biofilms. Parameria laevigata contains a variety of secondary metabolites, so that it has potential as an anti-biofilms. The purpose of this research was to examine the effect of the compounds contained in the bark of Parameria laevigata in forming biofilms. Methods: This systematic review research method was Systematic-Meta Analysis, which identifies research articles from journal databases including Microsoft Academic Search, Google Scholar, PubMed, and Science Direct. Meta-Analysis was used to analyze, determine, and interpret al. l the data in the systematically served articles. Results: Using a specific search prism guideline, the search result for research article found 28 research journals as primary data for systematic review research. The results of this systematic review showed that the bark of Parameria laevigata contains alkaloids, flavonoids, tannins, and saponins. Alkaloids can interfere with the components of peptidoglycan in bacteria. Flavonoids have able to inhibit the growth of microorganisms. Tannins have a role in influencing cell wall polypeptides so that the formation of cell walls becomes less than perfect. Saponins hydrolyze bacterial cell walls. Conclusion: The bark of Parameria laevigata has the potent activity to develop as antimicrobial by inhibiting biofilms formation mechanism.